A Plant design on the demineralization of Pasig River water - Alcaraz, Emma A.; Gonzales, Gisele G.; Ilao, Virginia V.; Mercado, Susana G. (Quezon City College of Engineering, 1979)
Our chosen plant site is the municipality of Pasig, Metro Manila, right along Pasig River. Electrical power is supplied by the Manila Electric Company (Meralco). Manpower is not a problem, and so is transportation. This plant which is designed to produce demineralized water from Pasig River water will have a capacity of 1.72 x 10^9 gallons of water per year, requiring a fixed capital investment of P 42,962,110. Waste disposal is not a problem, since the screenings are to be buried sufficiently deep to avoid odors, and shallow enough to permit bacterial activity. a cover of 12" to 18" porous earth would probably be found to give the best results. The sludge from the re-settling tanks are to be dumped back into the river.
Plant design
Submitted in partial fulfillment of the requirements in ChE 62
Keywords: Water treatment plants -- Design and construction